A German High Tournament Saddle in the Royal Armouries, Leeds. (3rd July 2015) - Viallon, Marina
Abstract : The Royal Armouries of Leeds preserves a rare example of an early fifteenth-century German tournament high saddle that is also one of the earliest complete western medieval saddles preserved. It bears witness to an extreme form of tournament which stood very far from the real practice of war: the Hohenzeuggestech. Impact marks of lances and swords, visible on the saddle, reveal the violence of the blows exchanged during these meetings, a violence often hard to observe in the contemporary but conventional representations of jousters and tourneyers. Thus, by the means of its excellent state of preservation, the Leeds high saddle sheds some light on the jousts and tourneys on high saddles, once so popular and plentiful in what remains of the civilian iconography of the late fourteenth- and the fifteenth-century Germanic world.